Exploring the role CD163-labeled TAMs and FOXP3-labeled Tregs in different types of breast cancer: Reflections and putative benefits - Lobna S Shash; Khaled A M. Kamal; Nermine M Abd Raboh (Wolters Kluwer Medknow Publications, 2021)
Context: Tumor immune microenvironment (TIME) is heterogeneous and dynamic. It exerts bimodal pro and antitumor effects. Among the TIME contributors, TAMs and Tregs are condemned as cancer cells allies rather than enemies; however, such contribution is not universally equal in all tumors. Aims: We aimed to explore and compare TAMs and Tregs in various breast cancers and link such findings to pathologic prognostic indices. Settings and Design: This was a retrospective study. Methods and Materials: Archival blocks of 108 breast cancers were immunohistochemically studied for CD163 and FOXP3 in tumor stroma (TS) and specialized DCIS periductal stroma. FOXP3 was additionally evaluated in tumor cells. CD163 and FOXP3 expressions were compared with different histopathological prognostic categories for statistical analysis. Statistical Analysis Used: Analysis of data was done using the Chi-Square test. Results: Both CD163+ TAM and FOXP3+ Tregs. showed statistically significant association with high tumor grade, T stage, multifocality and hormone negativity. Synchronous expression was consistent for both markers in almost all compared parameters, dual high expression of both CD163 and FOXP3 yielded additional statistically significant association with lymphovascular invasion (LVI). Periductal stromal CD163 and FOXP3 high expression showed statistically significant association with DCIS. FOXP3 tumor cells expression was similar to TS FOXP3 but additionally showed significant association with LVI and N stage; moreover, Her-2 over-expressing breast cancer was significantly associated with low FOXP3+ tumor cells. Conclusions: Breast cancer TS TAMs and Tregs. abundance reflects unfavorable prognosis in various breast cancers particularly hormone negative cancers.